2019
DOI: 10.1371/journal.pone.0214121
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and the analysis of multi-platform metabolomics data for the detection of intrauterine growth restriction

Abstract: Objective To interrogate the pathogenesis of intrauterine growth restriction (IUGR) and apply Artificial Intelligence (AI) techniques to multi-platform i.e. nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS) based metabolomic analysis for the prediction of IUGR. Materials and methods MS and NMR based metabolomic analysis were performed on cord blood serum from 40 IUGR (birth weight < 10 th percentile) cases and 40 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Using a metabolite set enrichment strategy, the raw data were analyzed to identify the metabolic pathways significantly perturbed in IUGR, which included: beta oxidation of very long fatty acids, oxidation of branched-chain fatty acids, phospholipid biosynthesis, lysine degradation, methionine metabolismthe urea cycle, and fatty acid metabolism. Since most of these metabolic activities involve the liver, the authors suggested that their results might indicate an abnormal fetal liver function in IUGR [65].…”
Section: Resultsmentioning
confidence: 99%
“…Using a metabolite set enrichment strategy, the raw data were analyzed to identify the metabolic pathways significantly perturbed in IUGR, which included: beta oxidation of very long fatty acids, oxidation of branched-chain fatty acids, phospholipid biosynthesis, lysine degradation, methionine metabolismthe urea cycle, and fatty acid metabolism. Since most of these metabolic activities involve the liver, the authors suggested that their results might indicate an abnormal fetal liver function in IUGR [65].…”
Section: Resultsmentioning
confidence: 99%
“…Recent metabolomics results in IUGR [5,47], even in relation to gut dysbiosis [48] and evaluating neonatal urines [49,50], and in GDM [51][52][53] are currently available in literature.…”
Section: Metabolomics In Obstetricsmentioning
confidence: 99%
“…Machine techniques can decode the high volume of data generated from a limited number of subjects, comparing them to traditional analytic approaches [5]. From a drop into the ocean (old biochemistry) to an ocean into a drop (metabolomics).…”
Section: Introduction: the Power Of Metabolomicsmentioning
confidence: 99%
“…These could include spectral profiles from high resolution mass spectrometry and metabolomic data from mass spectrometry and alternate modalities (i.e., NMR metabolomic spectra). [ 163 ] In addition, genomic data and pharmacogenomics is gaining traction in clinical institutions.…”
Section: Integration Of Ai and High Resolution Mass Spectrometry For mentioning
confidence: 99%